Motivations and attitudes towards the act of blood donation among undergraduate health science students - Gomes, Maria José (2018)
Undergraduate students are a target for blood donation, as they constitute a young healthy and well-informed group. Aim: To understand motivations and attitudes underpinning the act of blood donation among undergraduate health science students. Materials and methods: Cross-sectional study enrolling undergraduate students of a College of Health Sciences in the Northeast of Portugal (January/February, 2017). Data collection tool was a self-administered questionnaire covering questions about motivations (n = 8) and attitudes (n = 5) towards the act of blood donation. Participants were classified by donation status into donors (one previous donation) and non-donors (never donated). Multiple logistic regression models were used to assess the association between each attitude and motivation on donation status. Odds-ratio (OR) and respective 95% confidence intervals (95%CI) adjusted for potential confounders, were obtained. Results: Out of 362 participants, 12.7% (n = 46) had ever donated blood and 56.5% (n = 26) of them were regular donors. Out of 316 non-donors, 88.0% (n = 278) will donate blood under request. There were no differences between donors and non-donors regarding the attitudes towards blood donation. From all motivations only “be a civic duty” had a significant impact on donor status, such that participants reporting this motivation are more likely to be blood donors (OR = 2.58; IC95%:1.34-4.99) than their counterparts. Conclusion: This study revealed that 80.0% of undergraduate health science students are non-donors, but they are available to donate blood under request. Campaigns and advertising methods focused on the emergent needs for blood donation could play an important role in the recruitment of new donors among undergraduate students